Exploring the Transferability of Competency-Based Education Model to Social Work Education in Vietnam. Issue 6 (17th August 2016) - Han, Meekyung; Nguyen, Diana; Cohen, Edward; Drabble, Laurie; Nguyen, Hoa; Sen, Soma; Tran, Tuan
Abstract: The Socialist Republic of Vietnam (hereafter Vietnam) has made extraordinary strides in terms of economic progress during the past two decades. Such rapid economic change has also created many social problems such as poverty, family abuse, substance abuse, HIV/AIDS, and mental health problems. Vietnam has taken steps to develop workforce capacity to ameliorate such challenges by investing in social work educational programs, including participation in an international collaborative initiative, the Social Work Education Enhancement Program (SWEEP). This article describes the procedures and process of the initial stage of the development of a competency-based social work curriculum in Vietnam through SWEEP. More specifically, this paper presents the following collaborative strategies between partners in Vietnam and the SWEEP team in the United States: conducting a needs assessment; providing trainings on competency-based education (CBE) to the partners in Vietnam; and receiving feedback from the partners to grasp the challenges at the early stage of development of CBE in Vietnam. While this article focuses on Vietnam, the SWEEP project can be a reference from which to develop social work education in other countries in regard to global collaboration for development of social work curriculum based on the CBE model.